EKSISTENSI TATA PEMERINTAHAN ADAT DI MALUKU - Belyon Talabessy; Evan Tanalepy; Bayumi Kilbaren; Yunus Boger; Fricean Tutuarima; Louisa Metekohy (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Customary governance in Maluku, known through the terms negeri, ohoi, hena, and aman, is a valuable cultural heritage that has constitutional recognition based on Article 18B Paragraph 2 of the 1945 Constitution. However, its existence faces significant pressure from the currents of modernization and globalization that have the potential to erode the original identity of indigenous legal communities. This study aims to analyze the existence of this government structure in the midst of a modern state administration system. The method used is a qualitative approach with a literature study approach, which systematically examines scientific articles and regional regulations through content analysis techniques. The results of the study indicate that customary governance still exists structurally with the continued use of traditional nomenclature such as Raja, Badan Saniri, Kepala Soa, and Kewang in the regions of Central Maluku, Ambon, Seram, and Southeast Maluku. Field findings reveal the main challenges in the form of bureaucratization and selective legal recognition that often force the integration of customary systems into the formal village administration system, so that the essence of indigenous leadership is marginalized. The main conclusion emphasizes that while customary governance still operates according to tradition, a more serious regulatory commitment is needed to protect the flexibility of local systems from the threat of cultural homogenization. This governance system has proven capable of preserving the environment and social order if given genuine autonomy as a self-governing, independent, and sustainable community. ABSTRAK Tata pemerintahan adat di Maluku, yang dikenal melalui istilah negeri, ohoi, hena, dan aman, merupakan warisan budaya berharga yang memiliki pengakuan konstitusional berdasarkan Pasal 18B Ayat 2 UUD 1945. Namun, keberadaannya menghadapi tekanan signifikan dari arus modernisasi dan globalisasi yang berpotensi menggerus identitas asli masyarakat hukum adat. Penelitian ini bertujuan untuk menganalisis eksistensi struktur pemerintahan tersebut di tengah sistem administrasi negara modern. Metode yang digunakan adalah kualitatif dengan pendekatan studi kepustakaan, yang menelaah artikel ilmiah, dan regulasi daerah secara sistematis melalui teknik analisis isi. Hasil penelitian menunjukkan bahwa tata pemerintahan adat masih eksis secara struktural dengan tetap digunakannya nomenklatur tradisional seperti Raja, Badan Saniri, Kepala Soa, dan Kewang di wilayah Maluku Tengah, Ambon, Seram, hingga Maluku Tenggara. Temuan lapangan mengungkap tantangan utama berupa birokratisasi dan pengakuan hukum selektif yang sering kali memaksa integrasi sistem adat ke dalam sistem administrasi desa formal, sehingga esensi kepemimpinan asli menjadi terpinggirkan. Simpulan utama menegaskan bahwa meskipun pemerintahan adat masih berjalan sesuai tradisi, diperlukan komitmen regulasi yang lebih serius untuk melindungi fleksibilitas sistem lokal dari ancaman homogenisasi budaya. Tata kelola ini terbukti mampu menjaga kelestarian lingkungan dan tatanan sosial jika diberikan ruang otonomi murni sebagai komunitas pengatur diri sendiri secara mandiri serta berkelanjutan.